Employee green behavior: mapping knowledge structures and future directions - Winda Widyanty; Dian Primanita Oktasari; Setyo Riyanto; Dewi Nusraningrum; Sih Damayanti; Sik Sumaedi; I. Gede Mahatma Yuda Bakti; Anggini Dinaseviani; Prita Prasetya; Mochammad Fahlevi (Cogent Business & Management)
This study aims to provide an empirical analysis of publications in employee green behavior based on journal articles by revealing publication trends, impactful authors, leading journals, and the most influential articles. It also explores the knowledge structures including social, intellectual, and conceptual structure. This study used bibliometric and content analyses to analyze 429 journal articles on employee green behavior indexed by Scopus or Web of Science published between 1993 and March 2024. The results revealed increased interest and activity in studying employee green behavior over the past decade. The research has identified key bibliometric elements, namely impactful authors, leading journals, and the most influential articles. Further, this study has also described the knowledge structures including conceptual, intellectual, and social structure. We identified three clusters of research in the existing literature. The first cluster explores the role of organizational factors, the second examines the role of employee personal factors, and the third specifically focuses on the role of Green Human Resource Management (GHRM) practices. This study highlights the need for longitudinal studies to assess employee green behavior change over time, as well as which factors are most important among those previously identified. Comparative studies are also needed to understand the employee green behavior differences accross different cultural and organizational contexts.